2018
DOI: 10.1090/proc/13967
|View full text |Cite
|
Sign up to set email alerts
|

Some new computable structures of high rank

Abstract: Abstract. We give several new examples of computable structures of high Scott rank. For earlier known computable structures of Scott rank ω CK 1 , the computable infinitary theory is ℵ 0 -categorical. Millar and Sacks asked whether this was always the case. We answer this question by constructing an example whose computable infinitary theory has non-isomorphic countable models.The standard known computable structures of Scott rank ω CK 1 + 1 have infinite indiscernible sequences. We give two constructions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In general it is necessary that we look at equivalence classes to find the indiscernibles, as it was shown in [9] that every structure is bi-interpretable with one that has no triple of indiscernibles.…”
Section: ) (Where Pmentioning
confidence: 99%
“…In general it is necessary that we look at equivalence classes to find the indiscernibles, as it was shown in [9] that every structure is bi-interpretable with one that has no triple of indiscernibles.…”
Section: ) (Where Pmentioning
confidence: 99%
“…For some time the most important open question about structures of high Scott rank was whether there is a computable structure of Scott rank CK 1 whose computable infinitary theory is not ℵ 0 -categorical-which, by the corollary above, is exactly the same as asking for a computable structure of Scott complexity Π CK 1 +1 . Eventually Harrison-Trainor, Igusa, and Knight [7] provided such an example.…”
Section: The Standard Examples Of Computable Structures Of Scott Rank Ckmentioning
confidence: 99%
“…Proof. It is known that there exists a computable structure C of Scott complexity Π +1 ([13] for the case < CK 1 , and [7] for the case = CK 1 ). Let A be a computable structure of Scott complexity Σ +1 .…”
Section: A Has a D -σ α Scott Sentence If And Only If For Some C ∈ A (A C) Has A π αmentioning
confidence: 99%
“…Calvert et al [5] and Knight and Miller [12] found examples of computable structures with Scott rank CK 1 . Recently, Harrison-Trainor et al [8] gave examples of structures of Scott rank CK 1 whose computable infinitary theory is not ℵ 0 -categorical.…”
mentioning
confidence: 99%